Gentamicin graded challenge as an alternative therapy for cellulitis pedis in a patient with history of multiple drug allergies - Pinatih, I. G. Wahyu M.; Suryana, Ketut; Wulandari, Dewi C. (International Journal of Advances in Medicine, 2025)
Cellulitis pedis is a complication of diabetic neuropathy affecting the foot and most commonly caused by Staphylococcus aureus and Streptococcus pyogenes. A 55-year-old female patient presented with swelling and redness of the left foot that had persisted for one week. She had a history of type 2 diabetes mellitus and multiple drug allergies, including levofloxacin and cefadroxil. These comorbidities posed challenges in selecting an appropriate and safe antibiotic choice. Intravenous gentamicin was chosen as an alternative therapy in this case. A dose of 80 mg was administered using a graded challenge method to minimize the risk of severe hypersensitivity reaction.